Understanding Reasons for Lack of Effectiveness of National TB Program in Peru: Qualitative Analysis of MDRTB Control - Selene Manga; Michael R. Reich (International Journal of Thorax, 2024)
Drug-resistant tuberculosis (DR-TB) is the most urgent public health problem to solve in Peru, according to the Ministry of Health 1. In the WHO Global TB Report 2021, Peru has the highest burden of DR-TB in the Americas (Table 1), with 38% of TB cases either RR or MDR. In addition, the Ministry reports an estimated prevalence rate of DR-TB of 5.7% in new cases and 24.2% in previously treated cases. A total of 2493 new cases of DR-TB were reported in 2022, with 18.5% treatment dropout in 2019 believed to have increased by at least 52% in 2022 1. The post-pandemic context has created additional challenges for the control of DR-TB in Peru. A complex multiplicity of factors connects this disease to groups with high vulnerability, such as populations in extreme poverty and overcrowding or deprived of freedom; those who have immune system disorders, such as HIV and diabetes; and isolated indigenous populations.
Keywords: Rifampicin Resistant